2007
DOI: 10.1002/cncr.22526
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic radiation for lymphoma

Abstract: BACKGROUNDIonizing radiation has been used since the 1950s to treat a variety of cancers. Cancer patients who are treated with radiotherapy have shown increased risks for a variety of second malignancies, including mesothelioma, in several recent reports. The only existing study of Hodgkin lymphoma (HL) and subsequent mesothelioma had a short observation period.METHODSThe authors used Surveillance, Epidemiology, and End Results data over a 30‐year period to identify patients with HL and non‐Hodgkin lymphoma (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Of 10,578 patients with HL and 26,266 with NHL who received radiation therapy between 1973 and 2003, 14 developed mesothelioma as a second primary cancer. Teta et al [31] reported a statistically significant increase in mesothelioma risk among men with HL who received radiation (four Only one study examined mesotheliomas in individuals with primary testicular cancer. Travis et al [35] In a retrospective cohort study, Brown et al [36] analyzed treatment-related second cancers in a cohort of 376,825 1-year breast cancer survivors who were diagnosed between 1943 and 2002 and were reported to cancer registries in Denmark, Finland, Norway, and Sweden.…”
Section: Radiotherapymentioning
confidence: 97%
See 4 more Smart Citations
“…Of 10,578 patients with HL and 26,266 with NHL who received radiation therapy between 1973 and 2003, 14 developed mesothelioma as a second primary cancer. Teta et al [31] reported a statistically significant increase in mesothelioma risk among men with HL who received radiation (four Only one study examined mesotheliomas in individuals with primary testicular cancer. Travis et al [35] In a retrospective cohort study, Brown et al [36] analyzed treatment-related second cancers in a cohort of 376,825 1-year breast cancer survivors who were diagnosed between 1943 and 2002 and were reported to cancer registries in Denmark, Finland, Norway, and Sweden.…”
Section: Radiotherapymentioning
confidence: 97%
“…Teta et al [31] recently examined the incidence of mesothelioma in patients in the SEER database who received therapeutic radiation for HL or NHL. Of 10,578 patients with HL and 26,266 with NHL who received radiation therapy between 1973 and 2003, 14 developed mesothelioma as a second primary cancer.…”
Section: Radiotherapymentioning
confidence: 98%
See 3 more Smart Citations